2012
DOI: 10.1097/yco.0b013e328350360e
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and schizophrenia

Abstract: Schizophrenia and related psychoses are pervasive and debilitating conditions, for which currently available treatments are often only partially effective and entail a high risk of serious side effects. Thus, new therapeutic strategies are needed, and the literature reviewed here suggests that hormones such as oestrogen could be a viable option. It is hoped that, with further research and larger trials, the oestrogen hypothesis can be translated into effective clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 64 publications
2
44
0
1
Order By: Relevance
“…This smoother course of the disorder associated to a later onset of the frank episode of psychosis was attributed to the protective effects of estrogens in women (Reicher-Rossler et al, 1994;Seeman and Lang, 1990;Kulkarni et al, 2012). An older age of onset also allows the development of social skills and experience, and favors better coping with the difficulties and problems generated by the disorder and its consequences.…”
Section: Clinical Implications Of the Findingsmentioning
confidence: 94%
See 1 more Smart Citation
“…This smoother course of the disorder associated to a later onset of the frank episode of psychosis was attributed to the protective effects of estrogens in women (Reicher-Rossler et al, 1994;Seeman and Lang, 1990;Kulkarni et al, 2012). An older age of onset also allows the development of social skills and experience, and favors better coping with the difficulties and problems generated by the disorder and its consequences.…”
Section: Clinical Implications Of the Findingsmentioning
confidence: 94%
“…Alcohol and drug abuse appeared significantly more often among men, impacting on social functioning (Køster et al, 2008). Conversely, estrogens were supposed to modulate dopaminergic hyperactivity in females, thus leading to a smoother course of the disorder and a later onset of the frank episode of psychosis (Reicher-Rossler et al, 1994;Seeman and Lang, 1990;Kulkarni et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Consistently, while we demonstrated that Rasd2-targeted deletion prominently enhanced Amphand PCP-induced motor stimulation in both genders, we found that knockout females were protected against PPI dysfunction, seen in males. Given the established role of estrogen hormones in regulating the onset and severity of symptoms in patients with schizophrenia (Kulkarni et al, 2012), the gender-dependent PPI responses found in Rasd2 mutants represent an intriguing translational feature to decipher in future experiments. Accordingly, this preclinical model may provide a valuable in vivo tool to unveil the molecular determinants underlying the obscure interaction among sexual hormones and sensorimotor gating processes reported in humans (Kumari, 2011).…”
Section: Rasd2 Regulates Psychotomimetic Drug Effects D Vitucci Et Almentioning
confidence: 99%
“…Hormones have also been linked to the occurrence of schizophrenia, with oestrogen being protective (for a review see Kulkarni, Hayes, & Gavrilidis, 2012). Second, sex differences in interhemispheric transfer may provide an explanation (e.g., Nowicka & Fernsten, 2001).…”
Section: Bourne and Mckaymentioning
confidence: 99%